Revisiting and redefining the concept of retakaful and the viability of its model in Malaysian Takaful industry / Rosmi Yuhasni Mohamed Yusuf - Mohamed Yusuf, Rosmi Yuhasni (Faculty of Business and Management, 2011)
This paper aims to explore the concept of retakaful or Islamic reinsurance in Malaysia in the light of a dynamic development of the takaful and retakaful industry which is gaining its momentum all around the world especially in the Islamic countries. The first part of this paper would concentrate on the basic shari‟ah principles which govern the transaction of retakaful and explanation on the importance of retakaful as a fardhu kifayah in Malaysia. The second part would deal with the basic mechanism, basis and methods of retakaful available which are similar to the one in conventional reinsurance. The last part of this paper would be focusing on the issue of choosing the most viable operating models that conforms to the shariah principles and the arguments on a few issues relating to the operational models based on a different school of thoughts within the circle of Islamic scholars.